PENANAMAN KARAKTER KEMANDIRIAN ANAK USIA 5-6 TAHUN DI TK ISLAMIYAH PONTIANAK - Martacipta, Meideti; Syukri, M.; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to describe the planning, implementation, and evaluation of the cultivation of the character of independence in children aged 5-6 years in TK Islamiyah Pontianak. This research method is a descriptive method with a qualitative approach. The research subjects were 2 teachers, and 11 children. Data collection techniques used are observation, interviews, and documentation. The results of the research show: (1) Planning for the cultivation of self-reliance character is not clearly described. However, in compiling the RPPH and SOP there are values of independence which are taken based on the basic competency indicators in the 2013 curriculum (2) Implementation of the inculcation of the character of independence, the teacher guides, supervises, and motivates and provides opportunities for children to carry out activities in accordance with the SOP and RPPH gradually with discipline and independence through various methods, especially the habituation method, example, and the method of conversing. (3) Evaluation of the inculcation of the character of independence is carried out through observation from the time the child arrives until the child goes home and through documentation of the child's development in the form of an achievement scale, observation notes, and children's work.